QUALITY OF EDUCATION – THE CORE VALUE OF HUMAN CAPITAL - Piperkova, Irina; Djambaska, Elizabeta; Lozanoska, Aleksandra (Institute of Economics - Skopje, Ss. Cyril and Methodius, 2022)
Education is the major building block of human capital. The purpose of this article is to investigate the level of quality in secondary education and analyze educational attainment trends in North Macedonia. The research focuses on Eurostat statistical data of the educational attainment level of the population in North Macedonia vis-a-vis EU average. Eurostat data on employment based on educational attainment level of the population present an overview of the importance of education for employment opportunities and economic prosperity of individuals. The paper also analyzes the quality of education in North Macedonia, using an online survey among high school students to assess their perception on the level of quality of education. Survey findings reveal significant weaknesses in the quality of education in North Macedonia, among which the most alarming is that students do not perceive causality between education and future benefits in life. Without focusing on improving quality of education, especially in terms of greater focus on applied knowledge and lifelong learning, the country cannot expect that education can be a driver of human capital, productivity and economic growth.
Keywords: human capital, educational attainment, quality of education, applied knowledge